(3JaSjQ BjI GdONGf (B( (3Ke ESJhi Edi GdSeGA hgi ONGf (B)s - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje (B( (3Ke GSJhi Edi GdSeGA hgj ONGf (B) (3CTGQ HGdONGf Edi eGOI GdSeGA aGdONGf Lh ef XdeGA ai efHY GdXdeI ef MjK GfgG efHY GdYOe s
(3BNQgG (B:s
(3GdMGedI ddchGcH GdSHYI hgj SHYI hGdjheGf NHQ GSekG jYfi GdeGOI hGdUhQI bhdg JYGdi (B( (3hChMi ai cd SeGA GeQgG (B) (3GTGQI Edi GdYbhd GdeaGQbI GdJi gi eMQcGJgG Ydi SHjd GdJThjb hGdJYTjb s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJaSjQ hYdhe GdbQBfs